PENGEMBANGAN LKPD BERBASIS LIVEWORKSHEET BERORIENTASI SOAL AKM UNTUK MENGOPTIMALKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH DASAR - Fauziah, Yesi Ulfah; Ratnaningsih, Nani; Lestari, Puji (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2023)
The lack of interactive learning media that is oriented towards AKM questions and based on problem solving has resulted in less than optimal mathematical problem solving abilities of elementary school students. One of the interactive media that can help students understand and solve problems with AKM questions is live worksheet-based LKPD media that is oriented towards AKM questions based on mathematical problem solving. This research aims to determine the procedures for developing interactive learning media, the effectiveness of the media, and determine the increase in students' abilities after using the media. This type of research is R & D (Research & Development) which uses the ADDIE development model. The subjects of this research were 28 students in class V-B at SDN 3 Tugu. Data collection techniques are observation, interviews, questionnaires and tests. Based on the validation results from material experts and media experts, the results were "valid" in the "very feasible" category, based on the results of user trials the results were "very good". Media effectiveness obtained an effect size of 1.733 with the interpretation of "strong effect". To increase problem solving abilities, the N-Gain was obtained at 0.26889 with "low" criteria. The normality test results obtained Sig.0.001 so that the data was not normally distributed, then a non-parameteric test was carried out with the Wilcoxon test and obtained Sig. (2 tailed) 0.000, so there is a significant increase in mathematical problem solving abilities